DIGITAL MARKETING STRATEGIES OF UZAIRWAYS: DRIVING GROWTH IN THE AVIATION INDUSTRY - Elyorbek Tuygunov Diyorbekovich; Inomjon Qudratov; Dibias Lazuardi Maulid; Uktamjonov Dilmurodjon Ismoiljon ugli; Normatov Sultonbek Feruz ugli (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Main Purpose In the competitive aviation industry, a company’s worth is becoming more and more tied to how relevant it is online and how strong its internal resources are. This study investigates the impact of digital marketing strategies, represented by Social Media Marketing (SMM) and Search Engine Optimization (SEO) disclosures, alongside company capacity, on the growth of Uzbekistan Airways. This quantitative study utilizes an explanatory research design, drawing on secondary data from audited annual reports and digital performance metrics. The sample tracks the airline’s performance over a number of years. The content-analysis index is used to measure digital marketing disclosure, and the natural logarithm of total assets is used to measure company capacity. Multiple linear regression analysis is used to test hypotheses.